War Economy, Governance and Security in Syria's Opposition-Controlled Areas. Issue 1 (6th April 2018) - Bojicic-Dzelilovic, Vesna; Turkmani, Rim
This paper explores links between the war economy and civilian security by using evidence from the three opposition-held areas in Syria. The study of Eastern Ghouta, Daraa and Atareb shows how different type of behavior by non-state armed groups engaged in criminal war economy, shaped by the broader war economy conditions, impacts on the ability of the local populations to address their security predicaments. Our findings will challenge the assumption prevalent in the scholarship on the war economy that civilian security is unequivocally undermined by insurgents' criminal war economy dealings. We show that in some local contexts a diverse range of economic choices and actors provide the local population with more opportunities to develop coping strategies by engaging in different parts of the war economy.